SUPPLEMENTARY MATERIAL: Machine learning-based analysis of glioma grades reveals co-enrichment - Garbulowski, Mateusz (Uppsala University, 2021)
Examining glioma grading processes is valuable for improving therapeutic challenges. One of the most extensive repositories storing transcriptomics data for gliomas is The Cancer Genome Atlas (TCGA). However, such big cohorts should be processed with caution and evaluated thoroughly as they can contain batch and other effects. Furthermore, biological mechanisms of cancer contain interactions among biomarkers. Thus, we applied an interpretable machine learning approach to discover such relationships. This type of transparent learning provides not only good predictability, but also reveals co-predictive mechanisms among features. In this study, we corrected the strong and confounded batch effect in the TCGA glioma data. We further used the corrected datasets to perform comprehensive machine learning analysis applied on single-sample gene set enrichment scores using collections from the Molecular Signature Database. Furthermore, using rule-based classifiers, we displayed networks of co-enrichment related to glioma grades. Moreover, we validated our results using the external glioma cohorts.

The dataset was originally published in DiVA and moved to SND in 2024.

Se engelsk version av beskrivningen för information.
Datasetet har ursprungligen publicerats i DiVA och flyttades över till SND 2024.
SUPPLEMENTARY MATERIAL: Machine learning-based analysis of glioma grades reveals co-enrichment
Keywords: gliomas; gliom; machine learning; maskininlärning; Bioinformatics (Computational Biology); Bioinformatik (beräkningsbiologi)